PENGARUH RETAIL MIX TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN SEBAGAI VARIABEL MEDIASI PADA PELANGGAN DJIKAN’S AUDIO & ACCESSORIES DI KARANGANYAR - Supriyanto, Ari (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2015)
The objective of the research are to analyses (1) effect retail mix on customer loyalty, (2) effect retail mix on customer satisfaction, (3) effect customer satisfaction on customer loyalty, (4) effect retail mix on customer loyalty, through customer satisfaction as the mediating variable. Population on this research are all customer of Djikan’s Audio & Accessories in Karanganyar. The samples of this research consist of 100 responden, taken with convenience sampling. To test the hypothesis, researcher using path analysis. The result reveals that (1) there is a significance effect between retail mix on customer loyalty (2) there is a significance effect between retail mix on customer satisfaction (3) there is a significance effect between customer satisfaction on customer loyalty, (4) customer satisfaction has mediate of the effect between retail mix on customer loyalty. The conclusion of this research that all hypothesis are supported. Implications of this study, increasing of the customer satisfaction can be used as a strategy to maintain and raising customer loyalty of Djikan's Audio & Accessories in Karanganyar. Advised to the companies to increasing customer satisfaction, aims to support the successful implementation of the retail mix and customer loyalty will be higher. Keywords: retail mix, customer satisfaction, customer loyalty.